Using Public Health Surveillance Data to Determine Hepatitis C Virus Exposure Among Live-Born Infants - Abdullah Saleh Alabdullah et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Hepatitis C virus (HCV) poses a significant public health challenge, especially with the rising incidence among women of childbearing age. This review explores the utility of public health surveillance data to identify and manage HCV exposure in live-born infants. Current strategies for maternal screening, infant follow-up, and surveillance data utilization are discussed, emphasizing gaps in policy and practice. The findings advocate for robust, standardized frameworks to mitigate vertical HCV transmission and improve neonatal outcomes. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/298 DOI: https://doi.org/10.5281/zenodo.14581702